THE APPLICATION OF SLEEP HYGIENE THERAPY IN ELEMENTARY SCHOOL AGE CHILDREN WITH SLEEP DISORDERS PROBLEMS IN SERENGAN VILLAGE - Dwi Lestari Mukti Palupi; Ikrima Rahmasari (Proceeding of International Conference on Science, Health, And Technology, 2022)
Sleep is a repetitive neurobehavioral state of relative perceptual detachment and is not responsive to the environment, accompanied by a reclining position, calm behavior and closed eyes, which are important for health (Buysse, 2014). Sleep quantity disturbance is the non- fulfillment of normal sleep duration, which can result from difficulty initiating sleep or inability to maintain sleep. Sleep quality disorders are sleep interruptions due to awakening when sleep is of short duration but with frequent and repeated frequency (Cortese, et al. 2014). Sleep hygiene therapy is the most effective non-pharmacological therapy to overcome sleep pattern disorders (Yaremchuk, 2018). The general purpose of this case is to provide "The Implementation of Sleep Hygien in Elementary School Age Children with Sleep Disorders Problems in Serengan Village". The research method of this case study is descriptive in the form of family nursing care to explore nursing care problems for healthy school-age children. The research subjects used in this study were 1 client of school- age children who were in 1 family. The conclusion of the results of the problem of sleep pattern disorders in elementary school-aged children before the application of sleep hygiene was that they experienced sleep pattern disturbances with a total of 7 hours, after sleep hygiene the amount of sleep was 9 hours. Problems that arise before being given sleep hygiene are disturbances in sleep patternsand knowledge about sleep and rest after sleep hygiene problems are resolved